1991
DOI: 10.1002/app.1991.070420224
|View full text |Cite
|
Sign up to set email alerts
|

Thermoanalytical characteristics of polycarboxylic acids investigated as durable press agents for cotton textiles

Abstract: SYNOPSISPolycarboxylic acids are of great interest to the cotton textile industry as durable press agents because they do not release substances that require mandatory monitoring. Differential scanning colorimetric (DSC), thermogravimetric ( T G ) , and differential thermogravimetric ( D T G ) techniques were used to study the thermal characteristics of a series of 10 polycarboxylic acids. Samples included di-, tri-, and tetra-functional compounds some of which contained olefinic linkages, hydroxyl substituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Cross-linking interconnects the starch molecules through covalent bonding and increases the molecular weight, tensile strength, modulus and stiffness. Various cross-linking agents including sodium trimetaphosphate (STMP), sodium tripolyphosphate (STPP), epichlorohydrin (EPI) and phosphoryl chloride (POCl 3 ) have been used to cross-link starch. , Various nontoxic poly­(carboxylic acid)­s such as citric acid and 1,2,3,4-butane tetracarboxylic acid (BTCA) have also been used to cross-link cellulosic materials such as cotton, softwood kraft pulp fiber, etc., as well as starch. Cross-linking occurs when the carboxyl groups of the acid react with the hydroxyl groups present in starch to form an ester linkage .…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking interconnects the starch molecules through covalent bonding and increases the molecular weight, tensile strength, modulus and stiffness. Various cross-linking agents including sodium trimetaphosphate (STMP), sodium tripolyphosphate (STPP), epichlorohydrin (EPI) and phosphoryl chloride (POCl 3 ) have been used to cross-link starch. , Various nontoxic poly­(carboxylic acid)­s such as citric acid and 1,2,3,4-butane tetracarboxylic acid (BTCA) have also been used to cross-link cellulosic materials such as cotton, softwood kraft pulp fiber, etc., as well as starch. Cross-linking occurs when the carboxyl groups of the acid react with the hydroxyl groups present in starch to form an ester linkage .…”
Section: Introductionmentioning
confidence: 99%
“…At different BTCA concentrations the crosslinks will be different. The FTIR analysis reveals that at a lower concentration (2-8%) of BTCA there is a continuous increase in the size of the carbonyl peak with increasing BTCA; however, the relationship levels off at higher BTCA concentrations [7]. We believe this is mostly due to the ineffectiveness of the reaction of BTCA with the hydroxyl at high BTCA concentrations where some BTCA may not be linked with the macromolecules even by side grafts.…”
Section: Resultsmentioning
confidence: 88%
“…(2-8%) of BTCA there is a continuous increase in the size of the carbonyl peak with increasing BTCA; however, the relationship levels off at higher BTCA concentrations [7].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…with finish development. Our basic research studies were concerned with durable press reactants themselves, both formaldehyde [4] and nonformaldehydebased [ 5 ], various catalysts, and mixtures of reactants and catalysts [ 6 ] . We analyzed treated fabrics next to determine if the thermal characteristics were measurably different from untreated fabric and found that they were [ 7 ] .…”
mentioning
confidence: 99%